Analisis Komposisi dalam Cerpen “Pengantar Tidur Panjang” Karya Eka Kurniawan Kajian Morfologi - Listia Eka Sari; Dwi Alidya Safitri; Rido Pangestu (Yayasan Literasi Sains Indonesia, 2025)
This research aims to describe the composition in the long lullaby story by Eka Kurniawan Pokus in terms of word and phrase structure and how the use of morphology contributes to the meaning and aesthetic effects in literary works. and utilize various morphological processes, such as affixation, conversion, and composition, to build a unique and distinctive language style. The factor used in this research is the form of composition in a long bedtime short story. Then the data collection factor uses several factors, namely recording factors and data analysis factors, of these two factors are distributional factors. The results of this research are in composition form. And there are two compositions, namely exocentric and endocentric composition. And the results of the analysis were collected in 23 data containing composition elements, 10 data were exocentric, and 13 data were endocentric. It is hoped that this research will provide a deeper understanding of the use of morphology in literary works, especially in long lullaby short stories. Apart from that, it is also hoped that this research can become reference material for further research on morphological analysis in Indonesian literary works.